LEGAL PROTECTION FOR GOVERNMENT BANKS ON THE IMPLEMENTATION OF WRITE-OFF - Ambarwati, Mega Dewi; Suhessyani, Anggrita Esthi (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2022)
Write-off is a way to improve credit system of bank by moving a problematic loan that difficult to handle from bank's balance sheet become extracomptable therefore it will not burden the bank's performance later, however it does not remove the bank's right to collect as an effort to pay off problematic loans to the debtor. At a macro level, this research has a goal to improve the financial performance of banks by write off system. The specific objective is to provide legal protection for banks that carry out a write-off system and rescue problematic loans (credit) by write-off system. Statute Approach (Statute Approach) was done by reviewing every laws and regulations related to the write-off system of problematic loans in governmental banks. Conceptual Approach was done in order to maintain researcher to stay by the existing legal rules. While write-off mechanism is one of the efforts to save problematic loans that commonly used by banks. To decide whether problematic credit is included in the criminal law and corruption or not, it should be necessary to observe the process. Based on the description it can be concluded that as long as credit decisions that end up problematic are made based on business judgment, decided without a conflict of interest, and are accountable, it should not be criminally wrong.